A Brief History of Major Powder Metallurgy Research Centres. (1st January 2016) - Upadhyaya, G. S.
Abstract : The current article describes briefly the history of various research centres in powder metallurgy in various countries, based on the interaction which the author has made with the research scientists. The coverage includes Europe, North America, Asia and Australia.